2017
DOI: 10.1049/iet-cvi.2016.0462
|View full text |Cite
|
Sign up to set email alerts
|

Extracting statistically significant behaviour from fish tracking data with and without large dataset cleaning

Abstract: Extracting a statistically significant result from video of natural phenomenon can be difficult for two reasons: (i) there can be considerable natural variation in the observed behaviour and (ii) computer vision algorithms applied to natural phenomena may not perform correctly on a significant number of samples. This study presents one approach to clean a large noisy visual tracking dataset to allow extracting statistically sound results from the image data. In particular, analyses of 3.6 million underwater tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The experimental platform is generally composed of a computer, a camera and an aquarium, as shown in Figure 10. DL has shown good results in the fish behaviour recognition and analysis, which can verify certain laws, for example, the higher the water temperature is, the faster the fish swim 175 . Large‐scale losses of fisheries are often caused by the disease of individual fish, and mass death of fish is often accompanied by abnormal behaviour in the early stage of fish disease 176 .…”
Section: Applicationsmentioning
confidence: 87%
See 1 more Smart Citation
“…The experimental platform is generally composed of a computer, a camera and an aquarium, as shown in Figure 10. DL has shown good results in the fish behaviour recognition and analysis, which can verify certain laws, for example, the higher the water temperature is, the faster the fish swim 175 . Large‐scale losses of fisheries are often caused by the disease of individual fish, and mass death of fish is often accompanied by abnormal behaviour in the early stage of fish disease 176 .…”
Section: Applicationsmentioning
confidence: 87%
“…DL has shown good results in the fish behaviour recognition and analysis, which can verify certain laws, for example, the higher the water temperature is, the faster the fish swim. 175 Large-scale losses of fisheries are often caused by the disease of individual fish, and mass death of fish is often accompanied by abnormal behaviour in the early stage of fish disease. 176 DL networks, combined with the Directed Cycle Graph (DCG) and Dynamic Time Warping (DTW), can effectively detect the abnormal behaviour of fish to determine the cause of diseases or death.…”
Section: Behaviour Analysismentioning
confidence: 99%
“…needs the support of video-based approaches. For instance, Beyan et al [43] demonstrated through analysis of 12,247 videos that, as the water temperature increases, the swimming speed of fish increases. Xu et al [44] analyzed the abnormal behavior trajectory, movement volume, and movement speed of sturgeon, bass, and crucian carp in different stages of acute ammonia nitrogen stress-recovery experiments through video monitoring, in order to alert whether ammonia nitrogen in aquaculture water was abnormal.…”
Section: Limitation and Future Workmentioning
confidence: 99%
“…The raw data might not be consistent all the time, they might contain empty values or incorrect values, and sometimes they even contain data that are irrelevant from an analysis perspective. These inconsistencies in the data could result in a disputed outcome that might include the failure of the entire model that is built [22]. As a result, the dataset needs to be reconsidered, after refining the data it contains-after removing unnecessary information, which could be overwhelming, and cleaning data by removing disparities.…”
Section: Preprocessing and Cleaning Datamentioning
confidence: 99%
“…Support Vector Regression (SVR) model is an advancement to the conventional Support Vector Machines (SVM)-which are widely used for solving the problems that are of classification categories [22]. The aim of SVR is to obtain a hyperplane-after boosting the dimensions of the dataset-and organize them into distinct classes.…”
Section: Support Vector Regressionmentioning
confidence: 99%